Pemberian Terapi Murrotal Qur'an dan Sholawat Terhadap Kecemasan Ibu Bersalin Sebelum Operasi Sectio Caesarea di Rumah Sakit Bhakti Mulia Jakarta Barat Tahun 2024 - Jamilah Jamilah; Meylia Mahardhita (Jurnal Ners, 2025)
Until now, most people think that caesarean section is a scary experience. According to WHO, in 2022, anxiety will contribute around 15% of global morbidity rates. One of the non-pharmacological therapies to reduce anxiety is providing Qur'an murrotal therapy and sholawat.In 2024 to determine the impact of sholawat and murrotal Qur'an therapy on the anxiety levels of mothers giving birth before to caesarean section surgery at Bhakti Mulia Hospital in West Jakarta.Pretest and posttest design in a quasi-experiment with two groups. Purposive sampling was used to select 74 ladies who wished to give birth via elective SC between November and December 2024. The Independent T-Test was used to analyze the data, which had already been checked for homogeneity and normality.According to the univariate study's findings, women' average anxiety levels before caesarean section surgery and after receiving murrotal Qur'an therapy dropped by an average of 13.08. The average difference between the anxiety levels of moms who gave birth before caesarean section surgery and after the prayer was heard was 14.08. results of an independent T-test with a p-value of 0.862.The impact of prayer and the murotal Qur'an on the anxiety levels of pregnant women with preeclampsia is the same. In order to become closer to Allah and to bring comfort and serenity into their lives, mothers who are anxious before having a caesarean section should practice sholawat or murotal Qur'an therapy at least twice a day for fifteen minutes.